Avaliação operacional do Programa de Controle da Hanseníase nas unidades de saúde do Distrito Dagua no município de Belém-PA - SOUZA, Hilma Solange Lopes (Universidade Federal do Pará, 2015)
This paper describes the operational evaluation of the actions of leprosy control program in health units of Guamá administrative district from the municipality of Belém in the state of Pará. It is a quantitative ecological study in transversal type. Performed in the period from 2005 to 2010 in 12 health units as 05 health centers and 07 homes for families. Data were obtained through secondary SINAN related to 05 operational indicators used by the Ministry of Health to evaluate the program's control and data Leprosy primaries collected through interviews with health professionals and meet the ethical standards for research involving humans Resolution 196/96 CNS / MS. The results were: detection rate in the period from 22,6 to 39,7 cases per 100.000 leprosy too high according to the parameters of the MS. In the evaluation of disability at the moment of diagnosis the result found was regularly (81.3%) taking into account the total reported cases. Results showed a precarious to check the degree of incapacity of healed cases throughout study period. As the discharge healed the percentage found was above 90% in most units. It was observed that treatment dropout in units of Dagua District remained stable showing percentage below 10% in six (6) of the eleven units. It was identified that the units in Terra Firme neighborhood contributed to rising discharge percentage for dropout. In an interview realized with professional about training received the association between the variables ability to diagnose and treat leprosy and complications and/or reactions to the variables, age, professional category and length of service. It was found that the variable length of service was considered statistically significant. It concludes that the quality of service in these district units is beneath commended depending on the actual role of services and also the coverage lack of family health teams, causing the actions commended during disease monitoring treatment are not effective. It confirms that the control of leprosy as a public health problem in Dagua District in Belem requires additional surveillance measures, beyond those that are currently being used, it is important the management implementation to enable the coverage of services with skilled manpower to develop actions of promotion control and prevention of the problem.